A Case of Methanol Poisoning in a Child - Reyner Loza; Dimas Rodriguez (Case Reports in Nephrology)
We report the case of a girl admitted to the emergency room with a history of four hours' acute illness, characterized by nausea, vomiting, salivation, headache, blurred vision, and acidotic “Kussmaul” breathing. Arterial blood gases showed severe mixed acidosis, metabolic and respiratory with high anion gap. She had ingested the contents of a scent bottle containing methanol, which she thought was a soft drink bottle. The girl was managed with hemodialysis and strong intravenous hydration. She improved well and made a full recovery.